Cardiac events within one year after a subarachnoid haemorrhage: The predictive value of troponin elevation after aneurysm occlusion. (29th August 2020) - Akkermans, Annemarie; Peelen, Linda M; van Waes, Judith A; Rinkel, Gabriël J; van Klei, Wilton A
Abstract: Background: Patients who survive after an aneurysmal subarachnoid haemorrhage (ASAH) have an increased incidence of cardiovascular events compared with the general population. We assessed whether troponin elevation after aneurysm occlusion, as marker of myocardial injury, can predict long-term cardiac events. Methods: We analysed a prospectively collected cohort of 159 patients with ASAH and early aneurysm occlusion, in whom routine post-intervention troponin I (TnI) measurements were performed. With competing risk regression modelling we estimated the association between TnI elevation after aneurysm occlusion and major adverse cardiac events within one year. Secondary outcome measures were all-cause mortality and neurological condition within one year. The predictive value of post-intervention TnI was compared with the predictive value of pre-intervention characteristics using c-statistics and the integrated discrimination improvement index. Results: Subdistribution hazard ratios for TnI elevation and major adverse cardiac events at one year were 1.05 (95% confidence interval (CI) 1.03–1.07) per 10 ng/l increase in TnI and 7.91 (95% CI 1.46–43.0) for any TnI elevation. After adjustment for pre-intervention variables, the subdistribution hazard ratios were 1.47 (95% CI 0.81–2.67) per 10 ng/l and 9.00 (95% CI 1.62–50.1) for any elevation. The c-statistic was 0.71 for TnI elevation as a continuous measure and 0.69 for any TnI elevation. The integrated discrimination improvement index showed a minimum improvement in prediction of 0.08 (interquartile range 0.06 to 0.09) for TnI as a continuous measure and 0.003 (interquartile range −0.004 to 0.01) for any TnI elevation, when compared with pre-intervention characteristics. Conclusion: TnI elevation after occlusion of a ruptured intracranial aneurysm predicts the occurrence of a major adverse cardiac event within one year after ASAH.